2004
DOI: 10.1080/02652030410001721457
|View full text |Cite
|
Sign up to set email alerts
|

Determination of malachite green residues in rainbow trout muscle with liquid chromatography and liquid chromatography coupled with tandem mass spectrometry

Abstract: A method for the determination of malachite green and its major metabolite leucomalachite green in rainbow trout muscle is reported with limits of detection of 0.8 and 0.6 microg kg(-1), respectively. Residues were extracted with an acetonitrile-acetate buffer mixture and partitioned into methylene chloride. Clean-up of the extracts was performed on alumina and propylsulfonic acid solid-phase extraction columns using the automated solid-phase extraction system. The chromatographic separation of malachite green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…The LMG levels in the three species were correlated significantly with lipid content in the fish tissue. Earlier findings indicated that the distribution of LMG was related to the fat content of fish, such as channel catfish and rainbow trout (Poe and Wilson, 1983;Máchová et al, 1996;Tarbin et al, 1998;Halme et al, 2004;Mitrowska et al, 2005). Bauer et al (1988) found that the half-life of LMG in muscle was positively correlated with muscle lipid content and ranged from 10 to 40 days in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…The LMG levels in the three species were correlated significantly with lipid content in the fish tissue. Earlier findings indicated that the distribution of LMG was related to the fat content of fish, such as channel catfish and rainbow trout (Poe and Wilson, 1983;Máchová et al, 1996;Tarbin et al, 1998;Halme et al, 2004;Mitrowska et al, 2005). Bauer et al (1988) found that the half-life of LMG in muscle was positively correlated with muscle lipid content and ranged from 10 to 40 days in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, developing sensitive and simple method for the determination of BG is of great importance and interest in chemical analysis. Since today some techniques for the determination of trace amounts of malachite green (MG) have been reported (Halme and Lindfors, 2004;Pourreza and Elhami, 2007;Afkhami et al, 2010;Nicolle et al, 2011;Cheng, 2009;Lee et al, 2006;Jesu´s Martı´nez Bueno, 2010;Bahram, 2011), but the reports for the determination of BG are very scarce. Some of these techniques are spectrophotometry (Es'haghi, 2011), dosimetry (Khan, 2002); but these techniques are expensive and time consuming.…”
Section: Introductionmentioning
confidence: 98%
“…For the determination of MG in fish farming water, a spectrophtometric method was reported (Pourreza and Elhami 2007). A series of LC methods for the determination of MG in different kinds of matrix have been developed with fluorescence (Ramos et al 2003), MS (Wu et al 2007;Valle et al 2005;Hall et al 2008) and MS/MS detection (Bergwerff and Scherpenisse 2003;Halme et al 2004;Scherpenisse and Bergwerff 2005;Lee et al 2006;Mitrowska et al 2008). However, MG, EN-FLX and CPFLX used as veterinary medicine in aquiculture altogether have not been determined simultaneously.…”
Section: Introductionmentioning
confidence: 98%